2002
DOI: 10.1152/ajpgi.00388.2001
|View full text |Cite
|
Sign up to set email alerts
|

Alcohols enhance caerulein-induced zymogen activation in pancreatic acinar cells

Abstract: Activation of zymogens within the pancreatic acinar cell is an early feature of acute pancreatitis. Supraphysiological concentrations of cholecystokinin (CCK) cause zymogen activation and pancreatitis. The effects of the CCK analog, caerulein, and alcohol on trypsin and chymotrypsin activation in isolated pancreatic acini were examined. Caerulein increased markers of zymogen activation in a time- and concentration-dependent manner. Notably, trypsin activity reached a peak value within 30 min, then diminished w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
51
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 27 publications
3
51
1
Order By: Relevance
“…Treatment of acinar cells with ethanol alone (100 mM) for 15 min had no effect on protease activity, a result consistent with previous work (18). However, administration of ethanol (100 mM) for 15 min before physiologic carbachol (1 M) stimulation caused a 2-fold increase in both trypsin and chymotrypsin activities above unstimulated controls (p Ͻ 0.02; Fig.…”
Section: Ethanol Enhances Carbachol-induced Protease Activation-supporting
confidence: 91%
See 3 more Smart Citations
“…Treatment of acinar cells with ethanol alone (100 mM) for 15 min had no effect on protease activity, a result consistent with previous work (18). However, administration of ethanol (100 mM) for 15 min before physiologic carbachol (1 M) stimulation caused a 2-fold increase in both trypsin and chymotrypsin activities above unstimulated controls (p Ͻ 0.02; Fig.…”
Section: Ethanol Enhances Carbachol-induced Protease Activation-supporting
confidence: 91%
“…The findings confirm recent work by Lugea et al (20). Previous studies from Gorelick and colleagues (18,33) demonstrated that ethanol sensitizes the acinar cell to CCK-induced protease activation, but they were not able to detect sensitization of ethanol to carbachol using a carboxypeptidase A1 zymogen conversion assay (33). However, both our study and that of Lugea et al (20) used selective fluorescent protease substrates, which are more sensitive in measuring changes in zymogen activity.…”
Section: Discussioncontrasting
confidence: 58%
See 2 more Smart Citations
“…8e12 These high UFAs seem pathogenically relevant because several studies show UFAs can cause pancreatic acinar injury or can worsen AP. 11e14 Ethanol may play a role in AP by distinct mechanisms, 3 including a worse inflammatory response to cholecystokinin, 4 increased zymogen activation, 15 basolateral enzyme release, 16 sensitization to stress, 7 FA ethyl esters (FAEEs), 17 cytosolic calcium, 18 and cell death. 19 Because the nonoxidative ethanol metabolite of fatty acids (FAs), FAEEs, were first noted to be elevated in the pancreata of dying alcoholics, they have been thought to play a role in AP.…”
mentioning
confidence: 99%